PERBANDINGAN STRUKTURAL CERPEN MALAM-MALAM PENUH RENGEKAN DAN SAAT PAGI BUTA DALAM KUMPULAN CERPEN MALAIKAT TANPA SAYAP KARYA IMAS YULI HERYANI - Amanda Naila Eka Putri; Revalian Amanda Firmanzah; Welsi Damayanti (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
This study aims to descriptively compare the narrative structure of two short stories–Malam-malam Penuh Rengekan (Nights Full of Whining) and Saat Pagi Buta (In the Dawn)–in the collection of Malaikat Tanpa Sayap (Angel Without Wings) by Imas Yuli Heryani. Analysing the differences and similarities of the intrinsic elements in the two short stories including theme, characters, plot, setting, point of view, style of language, and moral , a qualitative method with a descriptive approach was applied by identifying, classifying, and interpreting the data obtained. The results of the study show that the two short stories have similarities and differences in terms of story structure. The similarities are seen in the use of theme, characters, plot, point of view, and moral. The differences are seen in the use of setting and style of language. The implications of these findings for enriching the literary studies analysis in different structural approaches and varieties of story elements are discussed.